The Reflector - Battaglia, Jennifer (Meliora Press, 2021)
A comprehensive and holistic understanding of human anatomy is foundational to the care of patients. The Reflector is an innovative and interdisciplinary approach to the learning of human anatomy; it incorporates etymology, history, art, drawing, and reflective writing to integrate the learning of anatomical structures with the nonanatomical curriculum of the anatomy lab, thus establishing the foundation for a biopsychosocial approach to medicine. To develop visual skills, this work features drawings that illustrate the original inspirations for anatomical terminology while also providing the space to artistically reimagine these structures. Together, these activities enhance the comprehension and retention of anatomical information for application in medical sciences. The Reflector employs thought-provoking questions that emphasize humanity in anatomy, in order to prompt consideration of the anatomical structures beyond basic science. Reflecting on the experiences of anatomical dissections, specifically in relation to development of habits of mind necessary for patient- and family-centered care, continually connects students to the purpose of their studies - to become a knowledgeable, compassionate, self-aware, reflective, and skilled member of a healing profession. Edited by a medical student with a Master's of Science degree in Medical Humanities; an anatomical science faculty member dedicated to the holistically educated medical provider; an expert in visual learning and self-reflection; and a bioethicist, The Reflector is a valuable resource for all who want to understand the human in human anatomy.